Pathways to more sustainable woodfuel value chains - Schure, J. (CIFOR-ICRAF, 2021)
Funded by the European Union, the Governing Multifunctional Landscapes Sustainable Woodfuel project aims to contribute to knowledge, options and engagement for more sustainable woodfuel value chains across Sub-Saharan Africa.